(untitled) (Jurnal Adabiya, 2021)
Abstract This thesis entitled “VOCATIVES FOUND THE POEM OF THE COBRA-KING AND THE FROG-KING” is a study about vocatives in The Poem of The Cobra-King and The Frog-King. The aim of this study is to find out the functions of vocatives and types of vocatives also to find out the most dominant function and type of vocatives in The Poem of The Cobra-King and The Frog-King. The main theory used in supporting this study is a theory of vocatives as proposed by Zwicky (1974) and Bungin (2005). To support this study, the researcher employed a descriptive qualitative method since the data of this study are in the form of text. The result of this study indicates that there are two functions of vocatives found in this poem, such as Calls and Addresses. There are four types of vocatives found in this poem, namely Vocative that describes jobs, Vocative in the use of certain social words, Vocative based on characteristics and identity of the interlocutors, and Vocative based on the group of the interlocutors. The most dominant function of vocative found in this poem is the Addresses function that occurs 90 times or 80.36%, followed by Calls that occurs 22 times or 19.64%. While the most dominant type of vocative found is vocative in the use of social words became the most dominant types that occurs 85 times or 75.89% then followed by vocative based on the characteristics and identity of the interlocutors occurs 21 times or 18.75 %, vocative that describes jobs occurs 3 times or 2.67% and the last vocative based on the group of interlocutors occurs 3 times or 2.67 %.